Realm of IP emerging and dynamic investigate - Singhal, Kanhaiya (IIPA Digest)
Intellectual property is indeed a creation of human intelligence that is always present around us, both inside and externally, and on which we exist. It$1 (Bs critical to evaluate the influence of IPRs on creativity, the economy, and society, and afterwards put in place the necessary resources, tools, regulations, and authorities to enable a functional IP system. IPRs are increasingly taking on extra responsibilities as a result of the interplay between globalised markets, national authorities, and local norms. Though the roads we travelled were littered with glaring errors and dark alleys, the fact that we recognized the flaws and reimagined today$1 (Bs Intellectual Property says something else about us: we can change, just as the concept of property has transformed from tangible property to intangible assets to intellectual property in the era of digital transformation, the internet, and artificial intelligence. The notion of IPR has never been redundant or static; it has developed through time. This will continue to do that as new aspects of law & technology emerge on a regular basis.- Reproduced s